2018
DOI: 10.1103/physrevlett.120.074501
|View full text |Cite
|
Sign up to set email alerts
|

Impulsively Induced Jets from Viscoelastic Films for High-Resolution Printing

Abstract: Understanding jet formation from non-Newtonian fluids is important for improving the quality of various printing and dispensing techniques. Here, we use a laser-based nozzleless method to investigate impulsively formed jets of non-Newtonian fluids. Experiments with a time-resolved imaging setup demonstrate multiple regimes during jet formation that can result in zero, single, or multiple drops per laser pulse. These regimes depend on the ink thickness, ink rheology, and laser energy. For optimized printing, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 40 publications
0
44
1
Order By: Relevance
“…The time scales to characterize the viscoelastic thinning are the relaxation time, λ, which is the time for the strain to relax when an applied stress is removed, the visco-capillary time scale, t v = η 0 R 0 /γ, and the inertia-capillary time scale, t c = ρR 3 0 /γ, where R 0 is the filament radius, ρ the density, γ is the surface tension with air, and η 0 = η s + η p is the zero shear viscosity where η s and η p are solvent and polymeric viscosities, respectively. This defines two non-dimensional numbers, the Deborah number, De, and the Ohnesorge number, Oh (Bhat et al 2010;Turkoz et al 2018):…”
Section: Introductionmentioning
confidence: 99%
“…The time scales to characterize the viscoelastic thinning are the relaxation time, λ, which is the time for the strain to relax when an applied stress is removed, the visco-capillary time scale, t v = η 0 R 0 /γ, and the inertia-capillary time scale, t c = ρR 3 0 /γ, where R 0 is the filament radius, ρ the density, γ is the surface tension with air, and η 0 = η s + η p is the zero shear viscosity where η s and η p are solvent and polymeric viscosities, respectively. This defines two non-dimensional numbers, the Deborah number, De, and the Ohnesorge number, Oh (Bhat et al 2010;Turkoz et al 2018):…”
Section: Introductionmentioning
confidence: 99%
“…% concentrations if the ink thickness is less than 15 lm. This result is counter-intuitive because it has been previously shown that inks with lower yield stress 16 and viscosity 28 can be printed with lower laser energy values. However, for the higher ink thickness values, the result is intuitive as it takes more energy to print as the thinner concentration decreases.…”
mentioning
confidence: 86%
“…The LIFT process is captured using a time-resolved imaging setup, which is the same as those used in previous studies. 15,16 The images of the transfer process from a side view are obtained with a microscope (InfiniTube with a Mitutoyo 10 Â Objective) attached to a CCD camera (SPOT Insight IN1820). Illumination is provided by strobing a 25-ns plasma-discharge flash lamp (HSPS Nanolite) after a specified time delay relative to the second laser pulse.…”
mentioning
confidence: 99%
“…These two conditions are equivalent to jetting a single high-velocity droplet. Recent studies [15,37] showed that single-droplet production can be Fig. 3 a Average injection depth as a function of the jet velocity (bottom x-axis) and the incident laser fluence on the donor slide (top x-axis).…”
Section: Depth-controlled Injection For Direct Three-dimensional Liqumentioning
confidence: 99%
“…In standard LIFT, a thin layer (10-100 μm) of the liquid to deliver is coated onto a transparent donor slide. Upon absorption of a nanosecond laser pulse by an absorptive layer of the donor slide, a shockwave is generated, which produces a liquid microjet towards a receiver slide [14][15][16][17]. Thus, LIFT can directly deliver biologically relevant liquids over the two dimensions of the donor slide without any reloading steps.…”
Section: Introductionmentioning
confidence: 99%